Progressão tópica em textos orais de alunos do ensino médio: um estudo a partir da linguística do texto e da pesquisa-ação - Machado, Lara Niederauer (2018)
This Master‟s research was developed with third year high school students from a public school in Santa Maria (RS) between August and December 2016. It aimed to investigate how the analysis of oral text productions in classroom collaborates on the qualification of the production of deliberative debate from students in that level. Therefore, we proposed: (I) to investigate how the study of text progression from selected conversational maxims (Grice, 1982) helps students in the production and reconstitution of their oral texts; (II) to investigate how Action Research, with the support of Text Linguistics, can help high school students to increase their ability of text production, specifically, in the oral modality; (III) to investigate how the work proposal from topical progression helps high school students in the establishment of strategies to produce their texts. The theoretical studies that supported our action, both in scientific and in didactic terms, are linked to Text Linguistics: Beaugrande and Dressler (1981), Charolles (2002), Fávero and Koch (1994), Koch (1992, 2006, 2014a, 2014b, 2015), and Marcuschi (2008). Furthermore, we consulted studies on textual genres, more specifically oral textual genres and Portuguese language teaching from the perspective of Schneuwly (2004a), Travaglia et al. (2013), Dolz and Schneuwly (2004a), Dolz, Schneuwly and Noverraz (2004), Marcuschi (2001). Our methodological approach was Action Research, according to Thiollent (2008), Tripp (2005) and Burns (2010). For the analysis of the linguistic material, we organized frames of analysis from which we observed text progression from the organization and the relationship among the discursive topics of the text productions. Concerning the analysis and discussion of the data based on three text productions of the student called S05, we used conversational maxims, proposed by Grice (1982), and discursive/argumentative connectors, classified by Koch (1992, 2015), since we aimed not only at the progression or not of the text, but also at the relationships established among the topics. In diagnostic text production (DTP), S05 reached two levels in the topical organization. However, this configuration differed gradually over textual productions, reaching the third level in the following productions (initial and final). The relationships among topics, i.e., in the hierarchical plane, were based on explanations/rationales, corrections/definitions and specifications/generalizations. In addition, the topics related in different ways; however, we did not observe discontinuity in the linear plane. These findings allow us to conclude that the work proposal based on Action Research and Text Linguistics, as well as the didactic approach to textual progression from conversational maxims helped the students to produce texts in the oral language.